TEACHERS 'ANXIETY LEVELS IN FACING THE COVID-19 PANDEMIC (VIEWED FROM GENDER ASPECTS) - Fadillatul Nisa (State Institute of Islamic Studies Batusangkar, 2021)
This quantitative descriptive field study aims to determine the level of teachers’ anxiety in facing the Covid-19 pandemic from a gender perspective. It is urgently needed to be conducted since teachers has dual roles during the Covid-19 pandemic, in which they have to be educators as well as parents who help children in online learning process. At the same time, the learning system keeps changing, lack of students’ awareness in implementing health protocols, and many students who do not do school tasks are some reasons why teachers have anxiety in the pandemic Covid-19 era. The population of this study were 39 civil servant teachers at MTsN 2 Pesisir Selatan consists of 30 female teachers and 9 male teachers. Samples were taken by using total sampling technique. Data were collected through a questionnaire developed from the Hamilton Rating Scale for Anxiety (HRS-A). The data analysis technique used is descriptive statistical analysis. The results showed that female teachers had high anxiety level with a percentage of 62.76%. Meanwhile, male teachers had medium anxiety level with a percentage of 57.82%. It reflects that female teachers had higher anxiety level than male teachers by a difference of 4.94%.